Modeling Inner City Traffic Generated Air Pollution. - Gooi, Bee Sung; Ooi, Chee Pin; Koh, Hock Lye (2003)
Rapid urban development in many cities in Malaysia has given rise to traffic congestions during peak hours. to overcome this congestion foe,more roads are being planned and built to help ease traffic away from city centers. Hence city outer rings roads are been constructed to diverts traffic flow. The outer ring roads may, however cut right through some parts of inner city with high concentration of population.Traffic generated air pollution may pose hazards to health of people living in the vicinity of the roads.